Tuberculosis and malnutrition: The European perspective. Issue 4 (April 2023) - Ockenga, J.; Fuhse, K.; Chatterjee, S.; Malykh, R.; Rippin, H.; Pirlich, M.; Yedilbayev, A.; Wickramasinghe, K.; Barazzoni, R.
Summary: Tuberculosis (TB) is a leading infectious cause of death worldwide, despite ongoing efforts to limit its incidence and mortality. Although the European Region has made gains in TB incidence and mortality, it now contends with increasing numbers of multidrug- and rifampicin-resistant tuberculosis (MDR/RR-TB). Malnutrition is a major contributor to the burden of TB and may also be directly caused or enhanced by the onset of TB. The presence of malnutrition may worsen TB and MDR/RR-TB related treatment outcomes and contribute to growing TB drug-resistance. Preventing and treating all forms of malnutrition is an important tool to limit the spread of TB worldwide and improve TB outcomes and treatment efficacy. We carried out a scoping review of the existing evidence that addresses malnutrition in the context of TB. Our review found malnutrition increased the risk of developing TB in high-burden settings and increased the likelihood of developing unfavorable treatment outcomes, including treatment failure, loss to follow-up, and death. The potential impact of nutritional care and improved nutritional status on patient prognosis was more difficult to evaluate due to heterogeneity of patient populations, treatment protocols, and treatment durations and goals. High-quality trials that consider malnutrition as a major risk factor and relevant treatment target when designing effective strategies to limit TB spread and mortality are needed to inform evidence-based practice. In TB patients, we suggest that widespread and regular nutritional screening, assessment, and counselling, has the potential to increase effectiveness of TB management strategies and improve patient quality of life, overall outcomes, and survival.